PENGARUH PENILAIAN PRESTASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT IDANOTAE KABUPATEN NIAS SELATAN - Martina Ndruru (Universitas Nias Raya, 2023)
The purpose of this study was to determine the effect of work performance assessment on employee performance at the Idanotae Sub-district Office, South Nias Regency. The type of research used is the quantitative type, while the data source is from employees, with the population and sample in this study being as many as 30 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study show that the calculated value (9,932)>ttabel (1,701) at df= (N-k-1)= (30-1-1)=28 and a significant level of 0.00<0.05, it can be stated that the variable has a significant influence on the assessment of work performance on employee performance at the Idanotae Sub-district Office, South Nias Regency. The suggestions for this study are (1) To improve employee performance to the maximum, an assessment of employees should be carried out in accordance with work so that they are motivated in completing work. (2) To improve the ability to work, it is better that in every workspace a computer is needed so that it does not become an obstacle to completing work.